2016
DOI: 10.1002/jcph.773
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Omarigliptin, a Once‐Weekly Dipeptidyl Peptidase‐4 (DPP‐4) Inhibitor, After Single and Multiple Doses in Healthy Subjects

Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of omarigliptin, a novel once‐weekly DPP‐4 inhibitor, were assessed following single and multiple doses in healthy subjects. Absorption was rapid, and food did not influence single‐dose PK. Accumulation was minimal, and steady state was reached after 2 to 3 weeks. Weekly (area under the curve) AUC and Cmax displayed dose proportionality within the dose range studied at steady state. The average renal clearance of omarigliptin was ∼2 L/h. DPP‐4 inhibition rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 14 publications
6
45
0
Order By: Relevance
“…7 The upper bound of the 95%CI for the between-group difference in QTcP between omarigliptin and placebo was less than 10 milliseconds at all postdose times (range, 3.89-5.76 milliseconds; Table 2). The maximum placeboadjusted least-squares difference in QTcP during the postdose observation period was 3.66 milliseconds with a 90%CI of 1.56-5.76 milliseconds.…”
Section: Cardiodynamic Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…7 The upper bound of the 95%CI for the between-group difference in QTcP between omarigliptin and placebo was less than 10 milliseconds at all postdose times (range, 3.89-5.76 milliseconds; Table 2). The maximum placeboadjusted least-squares difference in QTcP during the postdose observation period was 3.66 milliseconds with a 90%CI of 1.56-5.76 milliseconds.…”
Section: Cardiodynamic Resultsmentioning
confidence: 98%
“…In a previous multipledose study, the observed arithmetic mean C max and AUC 0-168 h values for 25 mg omarigliptin administered once weekly for 3 weeks were 579 nM (231 ng/mL) and 22.1 μM·h (8.81 ug·h/mL), respectively. 7 Therefore, the supratherapeutic omarigliptin dose administered in this study yielded an approximate 8-fold exposure margin to the C max previously seen at the clinical dose (25 mg). A review of the pharmacokinetic data available to date from the omarigliptin clinical program demonstrates that the median T max generally occurs between 1 and 6 hours postdose in normal healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although many anti-hyperglycemic agents are available, most of them still fail to achieve optimal glycemic control resulting from poor medication adherence (Krishna et al, 2016). More than 100 million people in China are affected by Diabetes Mellitus; T2DM is the most common form, accounting for approximately 90% of all cases (Chapman et al, 2016;Chen et al, 2015b).…”
Section: Introductionmentioning
confidence: 96%
“…Compared to once-daily DPP-4 inhibitor (sitagliptin, linagliptin, vildagliptin, saxagliptin and alogliptin), omarigliptin is more potent to inhibit DPP-4 enzyme (Tan, 2016). Previous study of pharmacokinetics and pharmacodynamics in health subject showed that omarigliptin was supportive of a sustained and clinically meaningful effect; it enhanced medication persistence and adherence of patients, optimized glycemic control and also reduced the risk of complications (Krishna et al, 2016).…”
Section: Introductionmentioning
confidence: 96%